MEMBANGUN LOYALITAS PELANGGAN TOKOPEDIA: PERAN E-SERVICE QUALITY, PERCEIVED VALUE, DAN CUSTOMER TRUST - Hilman, Nadia Ulfa Agustin; Rahayu, Dede Sri; Lestari, Nadya Ayu; Syaiful, Rizal Fahmi (Jurnal Ekonomi Manajemen, 2025)
This study aims to examine the influence of e-service quality and perceived value on customer loyalty, both partially and simultaneously. The population of this study were active students of Siliwangi University who had shopped at Tokopedia, with a sample of 388 students. The research method used was verification analysis, with data analysis techniques in the form of multiple linear regression. The results of the study showed three main findings, namely E-service quality and perceived value together have a positive influence on customer loyalty. E-service quality has a positive influence on customer loyalty. Perceived value has a positive influence on customer loyalty.